COMMISSION FOR HETERO-IDENTIFICATION AND RACIAL CLASSIFICATION OF PARDO STUDENTS - Dantas, Adriana S. R.; Isidoro, Guilherme Augusto Vasconcellos [UNESP] (FapUNIFESP (SciELO), 2024)
How does the selection by quotas for entry into public higher education and the passage through a hetero-identification commission affect the perception of racial classification of pardo (brown) students who have entered a public university? This article seeks to answer this question based on a research that examined, through in-depth interviews, the perception pardo students have of their racial belonging and whether the selection by quotas and passing through a hetero-identification commission had any effect on their perception. The results show that these experiences have contributed to reshaping how the racial classification of some pardo students takes place.
COMITÉ DE HETEROIDENTIFICACIÓN Y CLASIFICACIÓN RACIAL DE ESTUDIANTES PARDOS
COMMISSION D’HÉTÉRO-IDENTIFICATION ET CLASSIFICATION RACIALE DES ÉTUDIANTS MÉTIS
Keywords: HETEROIDENTIFICATION COMMITTEES; PARDO; QUOTA SYSTEM; RACE